Recent Advances in Nutraceutical and Functional Food - Pushpaanjali.G1 , R.V.Geetha2 , Leslie Rani.S3 , Lakshmi.T4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Food is just fortified into nutraceuticals and functional food. Nutraceuticals or bioceutical is a pharmaceuticalalternative which claims nutritional sources. Functional foods are modified food which improve health byproviding benefits beyond those provided by traditional nutrients. Eating habits and trends in food productionand consumption have healthy environmental and social impacts.Blood pressure effects from differentnutraceutical products have been studied with the specific food rich in minerals, lipids, whole protein andamino acid. Nutraceuticals range from isolated nutrients, specific diets to genetically engineered designerfood herbal products and processed food such as cereals, soup and beverages. Recent experiment has shownthat it may also inhibit plaque formation by bacteria in the mouth by the basic mechanism of inhibitingbiofilm formation. Plaque is the primary cause of gingivitis.When there is an increased plaque accumulation,there is also an elevation of microbial count in the saliva and biofilm. The plaque deposition around thegingival margin constituting bacteria that are anaerobic and aerobic is capable of initiating periodontaldisease and destruction. Fruits and vegetables contain thousands of biologically active phytochemicals someof which likely interact in a number of ways to prevent disease and promote health. Rapid changes in dietand lifestyle may enhance the expression of the harmful genes, which manifests in a sequence. There is anemergence of chronic disease in developing countries. Both pharmaceuticals and nutraceuticals compoundsmight be used to cure or prevent diseases. Therapeutic injections like lipotropic injection are also shownto improve the result of diet and exercise.Compounds not suspected of having any antibacterial propertiessuch as pesticide were shown to increase the minimum inhibitory concentrations of antibiotics against astrain of staphylococcus aureus both alone and in conjunction with antibiotics where Carbapenem are oftenconsidered to have a broad spectrum of activity .